Rashba effect modulation in two-dimensional A 2 B 2 Te 6 (A = Sb and Bi; B = Si and Ge) materials via charge transfer - Wu, Haipeng; Tian, Qikun; Wei, Jinghui; Xing, Ziyu; Qin, Guangzhao; Qin, Zhenzhen (Nanoscale, 2025)
Designing two-dimensional (2D) Rashba semiconductors, exploring the underlying mechanism of the Rashba effect, and further proposing efficient and controllable approaches are crucial for the development of spintronics. On the basis of first-principles calculations, we here theoretically designed all possible types (typical, inverse, and composite) of Janus structures and successfully achieved numerous ideal 2D Rashba semiconductors from a series of five atomic-layer A 2 B 2 Te 6 (A = Sb and Bi; B = Si and Ge) materials. Considering the different Rashba constant α R and its modulation trend under an external electric field, we comprehensively analyzed the intrinsic electric field E in in terms of work function, electrostatic potential, dipole moment, and inner charge transfer. Inspired by the quantitative relationship between charge transfer and the strength of E in and even the α R , we proposed a straightforward strategy of introducing a single adatom onto the surface of a 2D monolayer to introduce and modulate the Rashba effect. Lastly, we also examined the growth feasibility and electronic structures of the Janus Sb 2 Ge 2 Se 3 Te 3 system and Janus-adsorbed systems on a 2D BN substrate. Our work not only conducts a detailed analysis of A 2 B 2 Te 6 -based Rashba systems but also proposes a new strategy for efficiently and controllably modulating the α R through the reconfiguration of charge transfer.